Upaya Meningkatkan Kemampuan Kognitif Anak Melalui Kegiatan Bermain Balok Di Tk Islam Babussalam Rambah - Roslamiah Roslamiah (JURNAL PENDIDIKAN ROKANIA, 2018)
This study aims to improve the cognitive abilities of children through playing block activities. The subject of the study were students in TK Islam Babbusalam in Rokan Hulu of group B. The result obtained that the cognitive abilities of children in the 35% cycle I and increased in the cycle II to 75%. Based on the study concluded that beam play activities can improve the cognitive abilities of children